Review of Baeolidia, the largest genus of Aeolidiidae (Mollusca: Nudibranchia), with the description of five new species - Carmona, Leila; Pola, Marta; Gosliner, Terrence M.; Cervera, Juan Lucas (Zootaxa, 2014)
This paper discusses the systematics of the aeolid genus Baeolidia Bergh, 1888. To date, this monophyletic genus is the most diverse within Aeolidiidae with sixteen valid species. Excluding Baeolidia cryoporos Bouchet, 1977, the genus is restricted to the Indo-Pacific and Eastern Pacific. Species of Baeolidia show a huge intrageneric variability in several morphological characters. Only oral glands, if present, may distinguish Baeolidia from other aeolidiids genera. Aeolidiella occidentalis Bergh, 1875, Aeolidiella faustina Bergh, 1900 and Spurilla orientalis Bergh, 1905 are transferred to Baeolidia but they are considered nomina dubia. Five new species, Baeolidia rieae sp. nov., Baeolidia variabilis sp. nov., Baeolidia lunaris sp. nov., Baeolidia gracilis sp. nov. and Baeolidia scottjohnsoni sp. nov. are described.